Characterization of Nannizziopsis guarroi with genomic and proteomic analysis in three lizard species. (9th October 2017) - Schneider, Juliane; Heydel, Tilo; Klasen, Linus; Pees, Michael; Schrödl, Wieland; Schmidt, Volker
Abstract: Fungal infections in captive as well as in free-living reptiles caused by emerging obligate pathogenic fungi appear with increasing frequency and give occasion to establish new and fast methods for routine diagnostics. The so-called yellow fungus disease is one of the most important and common fungal dermatomycoses in central bearded dragons ( Pogona vitticeps ) and green iguanas ( Iguana iguana ) and is caused by Nannizziopsis guarroi . The aim of this study was to prove reliability in identification of N. guarroi with Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) in comparison to molecular biological analysis of ribosomal DNA genes. In seven lizards from three different species, including central bearded dragons, green iguanas, and a European green lizard ( Lacerta viridis ), dermatomycoses caused by N. guarroi were diagnosed by isolation of the fungal pathogen as well as histopathological confirmation of the granulomatous inflammatory reaction in deep skin biopsies. With this survey, we proved that MALDI-TOF MS is a diagnostic tool for accurate identification of N. guarroi . Besides small subunit 18S rDNA (SSU) and internal transcribed spacer (ITS)1-5.8S rDNA, a large fragment of the large subunit of the 28S rDNA (LSU), including the domain (D)1 and D2 have been sequenced, for phylogenetical analysis. Large fragment of the LSU from N. guarroi has been sequenced for the first time. Yellow fungus disease in a European lizard species is described for the first time to our knowledge as well, which could be of importance for free-ranging populations of European lizards.